Features of the hemostatic system in patients with endometrioid ovarian cysts - I A Lapina; L A Ozolinya; L I Patrushev; N I Nasyrova; S V Avakian (IP Berlin A.V., 2015)
Objective: evaluation of the hemostatic system in patients with endometrioid ovarian cysts before and after treatment of various types of surgical exposures.Materials and methods. 90 patients with with endometrioid ovarian cysts were operated, depending on the method of surgical treatment and therefore divided into two groups. The study was prospective in nature. The patients then underwent a complete clinical and laboratory examination, genotyping of the most significant thrombophilic polymorphisms.Conclusions. The analysis showed a reduction in performance of hemostasiogram compensatory mechanisms even in the absence of pronounced changes of hemostasis. In such a situation it is very important to choose the least traumatic method of surgical treatment, which allows not only to preserve ovarian reserve, but also reduce the level of response to the hemostatic system of interventions.